The Booker T. Washington Papers, Vol. 14 : Cumulative Index. Edited by Louis R. HARLAN and Raymond W. SMOCK - Washington, Booker T., 1856-1915 (Book collections on Project MUSE., 2015)
Hailed by John Hope Franklin as "a major event by any standards," The Booker T. Washington Papers are, according to Benjamin Quarles, "of the greatest significance for the study of race relations in America." The project now draws to a close with Volume 14, the cumulative index to this collection of the selected writings and correspondence of the celebrated black educator and leader. This essential guide, which also features a complete bibliography of the writings of Booker T. Washington, will be an invaluable aid to historians. Collectors of the preceding thirteen volumes in the insightful, highly acclaimed series will not want to be without it.